Digital literacy in older people: a scoping review protocol (Research, Society and Development, 2022)
Objective: To identify studies that assess digital literacy in the literature and map the instruments that assess digital literacy in the elderly. Methods: A search of published literature in English, Portuguese and Spanish will be carried out in Medline, VHL – Bireme, EBSCOHOST, Scopus, Web of Science, Embase, Cochrane Library, PsycInfo, Pubmed and Psycarticles databases. Two authors will evaluate the title, abstracts and full texts for eligibility. A customized data extraction form will be used to extract data from the included studies, which will be: (1) studies involving older adults (age ≥ 60 years); (2) quantitative and intervention studies, studies with a transversal and longitudinal design, experimental or clinical studies, studies of instruments that aim to assess digital literacy in the elderly. Results: The extracted data will be tabulated, together with a narrative summary.